2014
DOI: 10.1186/1471-244x-14-196
|View full text |Cite
|
Sign up to set email alerts
|

Association of TPH-1 and TPH-2 gene polymorphisms with suicidal behavior: a systematic review and meta-analysis

Abstract: BackgroundIt is widely acknowledged that suicidal behavior (SB) has a genetic influence. As a consequence, molecular genetic studies have been mostly conducted on serotonergic genes. One of the most promising candidate genes of this system is tryptophan hydroxylase (TPH). Although there have been several positive studies associating TPH genes and SB, the evidence is not entirely consistent. Therefore, we performed a meta-analysis to gain a better understanding into this issue.MethodsThe meta-analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 70 publications
3
29
0
2
Order By: Relevance
“…Moreover, it is interesting that the participants with the AA/AC, AA/AT, L′S′/S′S′ genotype pattern group experienced more positive and less negative effects of cocaine, greater physiological response, and more daily cocaine use. These findings support prior literature that demonstrates that lower serotonin production associated with TPH1 A and TPH2 A is related to suicidality, alcoholism, and impulsive behavior (González-Castro et al , 2014, Nielsen et al , 1994, Nielsen et al , 1998, Slof-Op’t Landt et al , 2013, Staner et al , 2002). This indicates a potential genetic marker of vulnerability to cocaine addiction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, it is interesting that the participants with the AA/AC, AA/AT, L′S′/S′S′ genotype pattern group experienced more positive and less negative effects of cocaine, greater physiological response, and more daily cocaine use. These findings support prior literature that demonstrates that lower serotonin production associated with TPH1 A and TPH2 A is related to suicidality, alcoholism, and impulsive behavior (González-Castro et al , 2014, Nielsen et al , 1994, Nielsen et al , 1998, Slof-Op’t Landt et al , 2013, Staner et al , 2002). This indicates a potential genetic marker of vulnerability to cocaine addiction.…”
Section: Discussionsupporting
confidence: 90%
“…The tightly linked variants (rs1799913 and rs1800532) in TPH1 (originally designated TPH prior to the discovery of TPH2 ) have been associated with behaviors including suicidality (González-Castro et al , 2014, Nielsen et al , 1994), alcoholism (Nielsen et al , 1998), impulsive behavior (Staner et al , 2002), and with cerebrospinal fluid (CSF) 5-hydroxyindoleacetic acid (5-HIAA) levels (Jönsson et al , 1997, Nielsen et al , 1994). Specifically, male TPH1 A allele carriers have been shown to have lower levels of serotonin production as measured by CSF 5-HIAA levels (Jönsson et al , 1997) and decreased risk for suicide attempt (González-Castro et al , 2014, Nielsen et al , 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaanalysen zum häufig untersuchten A218C-Polymorphismus im Intron 7 des TPH1-Gens konnten die Häufung des A-Allels bei Patienten mit suizidalem Verhalten zeigen (4,47). Weitere Metaanalysen unterstützen den Einfluss von TPH1-Polymorphismen auf suizidales Verhalten (1,4,13,23,31,39,47). TPH2, eine zweite Variante des serotonergen Schrittmacherenzyms, scheint im Vergleich zu TPH1 eine wichtigere Rolle im Gehirn einzunehmen, da TPH1-knockout-Mäuse nur ein mäßig erniedrigtes Serotonin im Hippocampus und im frontalen Kortex aufwiesen (62).…”
Section: Tph1 Und Tph2unclassified
“…Hypothesis-driven studies have identified a number of potential candidate genes. These include the brain-derived neurotrophic factor ( BDNF ) [8], neurotrophic tyrosine receptor kinase 2 ( NTRK2 ) [9], serotonin 2A receptor ( HTR2A ) [10], and tryptophan hydroxylase ( TPH2 ) [11]. However, as the effect sizes of markers in these genes have been small, it is likely that suicidal behavior is influenced by many still unidentified genetic factors.…”
Section: Introductionmentioning
confidence: 99%